2012
DOI: 10.1603/an12008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance and Population Structure of Chinavia hilaris and Nezara viridula (Hemiptera: Pentatomidae) in Georgia Farmscapes Containing Corn, Cotton, Peanut, and Soybean

Abstract: Stink bugs are economically important pests that damage a wide range of crops in the southeastern United States. Stink bug feeding on developing cotton (Gossypium hirsutum L. ) bolls may result in reduced yield and loss of fiber quality; similarly, feeding on developing soybean [Glycine max (L.) Merr.] pods can reduce yield and seed quality. During 2009 and 2010, the seasonal abundance and reproductive biology of Chinavia hilaris (Say) and Nezara viridula (L.) were investigated in replicated 1.62–2.83-ha farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
(36 reference statements)
0
12
0
1
Order By: Relevance
“…For N. viridula, the irregular nymph stage peaks across multiple crops (Fig. 1D) suggested multivoltinism, a view supported by Sullivan (1981, 1982) and Herbert and Toews (2012), but the low densities and use of insecticide hindered our ability to accurately determine multivoltinism for this species.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…For N. viridula, the irregular nymph stage peaks across multiple crops (Fig. 1D) suggested multivoltinism, a view supported by Sullivan (1981, 1982) and Herbert and Toews (2012), but the low densities and use of insecticide hindered our ability to accurately determine multivoltinism for this species.…”
Section: Discussionmentioning
confidence: 73%
“…Insecticide treatments are sometimes warranted in corn adjacent to wheat (Reisig 2011). The predictable peak populations of stink bugs during squaring and the first WOB in cotton might permit more efficient usage of insecticides by timing an application to occur early in egg hatching or during the early instars, as suggested by Herbert and Toews (2012), preventing the peak populations of nymphs from developing. Including all species of stink bugs, reproductive stage soybean hosted the largest numbers of stink bugs, with cotton fields adjacent to soybean fields often hosting peak populations on the same day (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this reproductive phase, the stage from flowering to pod formation is important because the maximum stink bug infestation occurs in this stage (Biswas, 2013). The population of N. viridula at soybean reproductive stage is abundant (Herbert & Toews, 2012). Molina & Trumper (2012) reported that fifth instar nymphs to have a higher attraction than the adult females on the R7 and R8 of soybean pods stage.…”
Section: Copyright © 2020 Universitas Brawijayamentioning
confidence: 99%
“…The availability and suitability of each host plant that N. viridula is associated with varies spatially and temporally (Herbert & Toews 2012;Panizzi 1997), with each host species providing, in its different life stages, some combination of nutrition, water, shelter, and reproductive suitability (Panizzi 1997(Panizzi , 2000Velasco & Walter 1992). …”
mentioning
confidence: 99%